'DANGEROUS PERFECTION' AND AN OLD PUZZLE RESOLVED: A 'NEW' APULIAN KRATER INSPIRED BY EURIPIDES' ANTIOPE. (2nd June 2014) - VILLING, ALEXANDRA
<x xml:space="preserve">Abstract</x> An Apulian calyx krater attributed to the Underworld Painter that entered the British Museum in 1867 as part of the collection of the Duc de Blacas (GR 1867, 0508.1335, Vase F270) has long puzzled scholars on account of its enigmatic iconography, seemingly representing Orpheus and Cerberus in the Underworld. Yet cleaning of the vase some 50 years ago – hitherto unnoticed by scholarship – revealed Cerberus to be a regular single‐headed dog. Two additional heads were added during nineteenth‐century 'restoration' in the accomplished early nineteenth‐century Neapolitan restorers' workshops headed by Raffaele Gargiulo. A new reading of the scene identifies it as the dialogue between Amphion and Zethos, a key episode in Euripides' play Antiope that is also referred to in Plato's Gorgias as emblematic of the rival concepts of the 'active' and the 'contemplative' life.